2023
DOI: 10.1007/s00268-023-06924-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electrical Acupoints Stimulation Improves Spontaneous Voiding Recovery After Laparoscopic Cholecystectomy: A Randomized Clinical Trial

Abstract: Background Facilitating the recurrence of spontaneous voiding is considered to be a way to prevent urinary retention after surgery, which is of great importance in cholecystectomy. This study aimed to assess the effect of transcutaneous electrical acupoint stimulation (TEAS) on spontaneous voiding recovery after laparoscopic cholecystectom. Methods Participants who underwent elective laparoscopic cholecystectomy were randomly assigned to either the TEAS group or the sham group. Active TEAS or sham TEAS at spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 40 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Appendix B lists the 7 reports excluded by checking complete textual documents. Finally, this review included fourteen studies [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Appendix B lists the 7 reports excluded by checking complete textual documents. Finally, this review included fourteen studies [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies with 2865 participants were identified. The types of surgery included biliary surgery [ 20 ], anorectal surgery [ 21 , 24 , 25 , 27 , 29 , 31 ], gynecologic surgery [ 22 , 23 , 26 ], orthopedic surgery [ 28 , 30 , 32 ], and urinary surgery [ 33 ]. All studies provided data on the incidence of POUR [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ], and two reported information on post-void residual urine volume [ 23 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations